Web-Based Bread Sales Information System Case Study Ro Bakery and Cake - Ahmad Farhan; Fety Fatimah; Fitria Rachmawati (Universitas Ibn Khaldun Bogor, 2025)
A Case Study on a Web-Based Roti Online Sales Information System Cakes and Pastries by RO Despite RO Bakery & Cake's best efforts, digital technology has failed to keep up with the industry's rapid expansion. Several problems arise because of business operations that are still primarily manual. The time it takes for the sales administrator to get sales data from each shop and the frequent occurrence of missing or damaged papers are two common problems. An information system is required by RO Bakery & Cake to generate online papers and sales reports to streamline the company's operations and ensure timely delivery to the administrative staff at headquarters. The research was carried out using a waterfall model, which consists of the following stages: (1) data collection (through observation, interviews, and literature reviews); (2) data analysis; (3) system design based on analysis results; (4) system development (using PHP and an object-oriented programming paradigm) and (5) black box testing to ensure the system is functional. The result of this research is a web-based bread sales information system that has 2 users, namely admin and spg outlet. Each user has different access rights according to their respective job duties and responsibilities. The benefits of this research are expected to reduce the risk of delays and damage during the product request process because documents are received by the admin through the system in real time. In addition, the admin can view and present sales data in the form of tables and graphs as support in deciding.